The augmented reality-aided navigation system may improve rotational alignment of the tibial baseplate in total knee arthroplasty - Tsukada, Sachiyuki; Ogawa, Hiroyuki; Saito, Masayoshi; Minagawa, Shizuka; Kurita, Miki; Hirasawa, Naoyuki (BMC musculoskeletal disorders, 2025)
Background Tibial rotational alignment is the most prone to error among the placement angles of the prosthesis in total knee arthroplasty (TKA). The augmented reality (AR)-aided navigation system enables surgeons to visualize the tibial anteroposterior axis established on the pre-resection surface superimposed on the bone surface after proximal tibial resection. Methods We compared the axial, coronal, and sagittal alignments of the tibial baseplate between 58 TKAs performed using an AR-aided navigation system and 64 TKAs in which the rotational alignment was determined manually. To assess alignment, the three-dimensional coordinates of the lower limb from preoperative CT data were overlaid onto postoperative CT data using a surface-matching algorithm. Results The absolute difference between the anteroposterior axis and the rotational angle of the tibial baseplate was significantly smaller in the AR-aided group compared to the control group (3.7 ± 3.4° vs. 5.1 ± 4.4°, p = 0.047). In both coronal and sagittal alignments, the absolute differences between the target angle and the measured angle were not significantly different between the two groups (1.1 ± 0.9° vs. 1.2 ± 1.0°, p = 0.75 in coronal alignment, and 1.9 ± 1.3° vs. 1.7 ± 1.4°, p = 0.43 in sagittal alignment, respectively). Conclusions The AR-aided navigation system slightly but significantly improved the accuracy of tibial rotational alignment.